A hybrid robot for friction stir welding. (October 2015) - Li, Qinchuan; Wu, Weifeng; Xiang, Ji'nan; Li, Hongjun; Wu, Chuanyu
Friction stir welding (FSW) has been widely applied in a number of fields instead of traditional fusion welding. However, a huge axial downward force is required to maintain a steady welding process. Moreover, the task of welding along a curved surface requires an orientation ability, which traditional FSW machines cannot provide. To overcome this limitation, we propose a 5-axis hybrid robot for FSW. This hybrid robot comprises a 2-SPR-RPS parallel mechanism (with one translational degree of freedom and two rotational degrees of freedom) and two gantries. First, mobility of the parallel mechanism in the initial and general configuration is analyzed using screw theory and continuous rotational axes are identified. Second, forward and inverse position solutions to the hybrid robot are studied, and the Jacobian matrix of the parallel mechanism is obtained. By analyzing the motion/force transmissibility, the architectural parameters of the parallel mechanism are optimized. Finally, the reachable workspace of the end effector is obtained considering the constraints of actuation links, joint angles, and singular configuration.